Indigenous People and Customary Law in Case of Religious Rights: A Taste of Injustice from Karuhun Urang in Indonesia - TRIDEWIYANTI, Kunthi; Luh Rina APRIANI; Nurul MIQAT (Revista Jurídica Portucalense, 2024)
This study examines Indonesia's Adat Karuhun Urang (AKUR) Community and their religious rights and justice struggles. The study seeks to determine how AKUR perceives and experiences religious justice injustice. This research is ethnographic and descriptive. Participatory observation and in-depth interviews with AKUR members, community leaders, and relevant parties. The project has documented AKUR's religion, culture, and social relationships. AKUR's history and religious rituals are examined in light of customary law and Sunda Wiwitan. Religious discrimination affects identity documents, schooling, and marriage for AKUR. Constitutional Court rulings and government legislation address this injustice, but religious rights and private views remain unsettled. The research examines religious rights justice through Rawls and Nozick's theories. Unfairness against AKUR violates the fundamental right to religious freedom. Nozick's philosophical relationship between religious liberty and self-ownership is also examined. According to the report, the Indonesian constitution provides religious freedom for everybody. However, the legal separation of religion and belief discriminates against AKUR. The study stresses the importance of recognizing belief as a primary religion and protecting Indigenous groups' religious rights, including religious practices and beliefs.